Nanoformulação do [10]-Gingerol em células de câncer de mama triplo negativo - Baptista, Ideli Zanesco Fontes (Universidade Federal de São Carlos, 2020)
Breast cancer is the neoplasm that most affects women worldwide and can be classified into different types. Among them, triple negative breast cancer (TN) is characterized by not having hormone receptors, nor receptors for HER2. This type of cancer corresponds to approximately 20% of cases, has great metastatic potential, especially for vital organs such as bones, lungs and brain, and consequently has a worse prognosis. Due to its cellular characteristics, TN breast cancer does not have target therapies, and therefore the search for new treatments is extremely important. Thus, natural products are rich sources for the search for new molecules that can be applied to therapy against TN breast cancer, some of which have already been shown to have anti-tumor and anti-metastatic properties. Previous results from our research group have already demonstrated the effectiveness of the [10]-gingerol (10G) molecule in its cytotoxic and pro-apoptotic action in vitro and in vivo antimetastatic in animal models of TN breast cancer. However, due to its low solubility in aqueous buffers, its effectiveness may be reduced, especially in vivo. Thus, this study aimed to study a pharmaceutical formulation of 10G and verify its activity in vitro. The results obtained show that the formulated compound not only maintains its initial anti-tumor characteristics, but in some cases they are potentiated, indicating optimistic perspectives for possible in vivo tests.
Nanoformulation of [10] -Gingerol in negative triple breast cancer cells
Keywords: 10-gingerol; Câncer de mama; Câncer de mama triplo-negativo; Formulação; Nanoemulsão; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS